Effects of submental stimulation for several consecutive nights in patients with obstructive sleep apnoea. Issue 5 (May 1994) - Hida, W; Okabe, S; Miki, H; Kikuchi, Y; Taguchi, O; Takishima, T; Shirato, K
Abstract : BACKGROUND--It has previously been reported that short term submental stimulation can reduce the frequency of apnoea and improve sleep architecture in patients with obstructive sleep apnoea. The effects of submental stimulation during consecutive nights on apnoea or on daytime sleepiness have not, however, been studied. METHODS--Patients with obstructive sleep apnoea were studied by polysomnography on a control night, for five consecutive nights of submental stimulation, and on three following nights (n = 8). A multiple sleep latency test (MSLT) (n = 8) and measurement of the upper airway resistance (n = 5) were performed during the day after the polysomnographic study, on the control night, and on the fifth stimulation night. In an additional five patients with obstructive sleep apnoea, matched for age, sex, and weight, the effects of two nights of stimulation were examined for comparison. Submental stimulation began when an apnoea lasted for five seconds and stopped with the resumption of breathing as detected by oronasal flow. RESULTS--The apnoea index, the number of times per hour that SaO2 dropped below 85% (SaO2 < 85%/hour), and the total apnoea duration expressed as a percentage of total sleep time during stimulation nights decreased to approximately 50% of the corresponding values on the control night. This improvement persisted for at least two nights after the five consecutive stimulation nights, but not after the two consecutive stimulation nights. Sleep architecture and MSLT following the stimulation nights improved but upper airway resistance did not change. CONCLUSIONS--Submental stimulation for five consecutive nights in patients with obstructive sleep apnoea improved the breathing disturbance, sleep quality, and daytime sleepiness. The effect lasted for the following two nights, but did not completely abolish the sleep disordered breathing.